TECHNOLOGIES OF USING SILK FIBER WASTES IN THE PRODUCTION OF FILAMENTS USED IN BIOMEDICINE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article provides detailed information on the production of high-quality medical products in modern medicine, including methods for the effective use of silk fiber waste. Also, methods and technologies for the production of raw materials used in the preparation of filament products that are specifically intended for human health, harmless to human health, and beneficial not only from silk fiber itself, but also from waste generated during the production of silk fiber. These technologies play an important role in improving the quality of life of patients and improving the healthcare system.